Analisis Tindak Tutur Netizen Indonesia Terhadap Fenomena Monyet Punch di TikTok: Lokusi, Ilokusi, Perlokusi - Ines Amelia; Nur Syakila; Poppy Adelia Adisty; Tessalonika Simangunsong; Lolo Mesliana Cibro; Aulia Uswatun Siagian; Herning Puspitarini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Using pragmatics, this study aims to describe the speech acts of Indonesian netizens regarding the Punch monkey phenomenon on TikTok. The focus of the study is to find locutionary, illocutionary, and perlocutionary speech acts in netizen comments on TikTok. This study is a qualitative study using a descriptive approach. Data collection techniques were carried out through observation and documentation of comments on videos related to the phenomenon. The research data consisted of three comments that were purposively selected as analysis samples. Each comment was analyzed based on three dimensions of speech acts, namely locutionary, illocutionary, and perlocutionary as the effects they have on the reader. The results show that the three comments analyzed simultaneously contain locutionary, illocutionary, and perlocutionary elements. Comments in the locutionary aspect convey direct information about Punch's condition, while comments in the illocutionary aspect contain the intention of expressing sympathy, criticism, and support. Meanwhile, comments create emotional effects, such as empathy and concern for Punch's condition, in the perlocutionary aspect. These findings indicate that a single comment on social media can have a complex and layered communicative role. Therefore, the language used in social media comments not only serves to convey information, but also to express attitudes and influence readers.